Insights into the alteration of vaginal microbiota and metabolites in pregnant woman with preterm delivery: prospective cohort study - Wang, Lihua; Zhang, Jun; Zhang, Mengjun; Xu, Zhimin; Zheng, Yijing; Lv, Bingqing; Pan, Mian (Frontiers in Cellular and Infection Microbiology, 2025)
Disruptions in vaginal microbiota and metabolites during pregnancy may be the most important risk factor for preterm delivery, thus the difference in vaginal microbiota and metabolites between women who subsequently delivered at term and who eventually experienced preterm birth. In this study, 63 participants were enrolled before the cervical cerclage surgery (namely pre-cerclage), comprising women who subsequently delivered at term and who eventually experienced preterm birth. The cervical-vaginal fluid (CVF) was collected two days prior to the cervical cerclage surgery. Compared with the term birth groups (PrTG), the proportion of beneficial bacteria (Lactobacillus, Prevotella, Trichococcus, Neisseria and Gemella) in the preterm birth group (PrPG) were significantly reduced (p < 0.05), while the proportion of harmful bacteria (Thauera, Ochrobactrum, Gardnerella, Massilia, Phyllobacteriaceae and Atopobium) were significantly increased (p < 0.05). In addition, vaginal metabolomics-based LC-Orbitrap-MS/MS revealed that the contents of 2-Piperidone, Melphalan, N-acetylputrescine, Obatoclax, Eurostoside, Pregnanediol 3-O-glucuronide, O-Phospho-L-serine, 1-Kestose and N-arachidonylglycine were significantly decreased in the PrPG group compared with the PrTG group, while Acenocoumarol, Isopyrazam, Pentosidine, hexose, 7-Hydroxymitragynine, PE, Tamoxifen and 1-Deoxynojirimycin contents were significantly increased. These results suggest that specific bacterial species and metabolites may serve as potential biomarkers for preterm birth prediction, and approve the theoretical basis for the intervention of preterm birth.